Designing a Comprehensive Pattern of Structural-Psychological Empowerment for Employees of Medical Sciences Universities: - Roohollahi, Nayereh Sadat; Masoudi Asl, Iravan; Hessam, Somayeh; Mahmodi, Mahmoud (Galen Medical Journal, 2019)
Background: The concept of empowerment requires the abandonment of traditional models. The need to design and develop employee empowerment patterns has been emphasized in several studies. The present study aims to design a comprehensive structural-psychological empowerment pattern for employees of medical sciences universities. Materials and Methods: Our exploratory research was conducted on 410 employees of medical universities of Tehran, Iran, and Islamic Azad University. Firstly, a primary pattern was designed according to a review of available literature, texts, patterns, and tools. Then, the psychometric analysis was done using validation (face validity, content validity, construct validity, factor validity) and reliability (internal consistency and stability). Lastly, the final pattern was introduced after having been approved by experts. Data were analyzed using SPSS version 24 and AMOS made by USA IBM software. P<0.05 was considered as the significance level. Results: Based on our study, 83.9% of participants were holders of bachelor’s degrees or higher degrees. The results of validation (face, content, structure, and confirmation validity) and reliability (internal consistency [α=0.90] and stability [0.91] ) showed that the structural-psychological empowerment pattern was appropriate, which was validated with 31 items and 8 domains. The scope of this pattern included resources, self-sufficiency, competence, support, effectiveness, and opportunity, significance, and information domains. The highest impact on the model was related to the support domain (impact factor=0.87). Conclusion: The present pattern is an appropriate and verified Iranian model in the field of structural-psychological empowerment, which is suggested in the cultural context of Iran, especially in medical universities.